Bioassays and virtual screening to identify potent natural antifouling compounds from the brown macroalga Dictyota dichotoma - Ba-akdah Mohammad Abdulaziz; Satheesh Sathianeson (Oceanological and Hydrobiological Studies)
Macroalgae are one of the potential natural sources for the isolation of novel eco-friendly antifouling compounds. In this study, the antifouling activity of an extract of the brown macroalga Dictyota dichotoma collected from the Red Sea was tested against bacteria isolated from the marine biofilm and larval forms of the barnacle. A maximum inhibition of barnacle larval settlement of 89.36% was observed in 25 µg ml-1 extract concentration at 24 h treatment. The secondary metabolite composition of the extract was analyzed by GC-MS and compounds were used as ligands for molecular docking with barnacle cement protein. The toxicity profile of secondary metabolites present in the extract was predicted through in silico analysis. The results indicate that the crude extract of the alga inhibited the biofilm formation by the bacteria and significantly reduced the settlement of the barnacle larvae. GC-MS analysis of the extract revealed the presence of five metabolites, including two fatty acids. All metabolites showed higher binding affinity with barnacle cement than the reference compound, copper. Among the secondary metabolites detected in the algal extract, the cholestane derivative exhibited maximum binding affinity (–14.2 kcal mol-1) with barnacle cement. The metabolites also showed positive for crustacean and fish toxicity in toxicity prediction using an in silico method.